Evaluation Of Antidiabetic Potential Of Ethanolic Extract Of Leaves Of Ficus Bengalensis Linn - S. MANIKANDASELVI; R. SUBALAKSHMI; R.THINAGARBABU; R.RAVIKUMAR (International Journal of Pharma and Bio Sciences, 2012)
The aim of the present study was to evaluate the antidiabetic potential of ethanolic extract of Ficus bengalensis Linn. leaves in alloxan induced diabetic rats. The effect of different concentrations of ethanolic extract on glucose, heamoglobulin, urea, creatinine, uric acid, cholesterol, LDL, VLDL, HDL, protein, albumin, globulin, ALP and ACP level in diabetic rats was studied. Oral administration of ethanolic extract decreases the level of heamoglobulin, sugar, urea, uric acid, cholesterol, TGL ,LDL, VLDL, albumin, ALP, ACP and increase the level of HDL. Optimum dasage of 1ml/Kg/day was arrived on the basis of our experimental results.